Refractory tension pneumothorax as a result of an internally displaced thoracoamniotic shunt in an infant with a congenital pulmonary airway malformation. (28th July 2016) - Law, Brenda Hiu Yan; Bratu, Ioana; Jain, Venu; Landry, Marc-Antoine
Abstract : Antenatally, congenital pulmonary airway malformation (CPAM) causing fetal hydrops can be palliated with thoracoamniotic shunts, which may become displaced in utero. We report a case of an infant born at 34 weeks gestational age with an antenatally diagnosed macrocystic lung lesion, fetal hydrops and an internally displaced thoracoamniotic shunt. The infant suffered refractory pneumothoraces despite multiple chest drains, and stabilised only after surgical resection of the lesion. Intraoperatively, the shunt was noted to form a connection between a type I CPAM and the pleural space. As the shunt was displaced internally, this complication was not immediately obvious during the initial resuscitation. In infants with large cystic lung lesions, clinicians should be aware that internally displaced thoracoamniotic shunts could contribute to refractory tension pneumothoraces and anticipate the need for advanced neonatal resuscitation, including early thoracocentesis or chest drain insertion. Furthermore, displaced shunts may require early surgical intervention.